The Role of Green Finance in Investing in Environmentally Friendly Technologies: Risks and Returns - Erdoğdu, Aylin; Dayi, Faruk; Özbek, Adem; Ganji, Farshad; Benek, Ayhan (MDPI AG, 2025)
This study offers a comprehensive analysis of the performance and systemic dynamics of green finance investments in environmentally sustainable technologies from 2000 to 2025, complemented by scenario-based projections extending to 2050. Empirical results indicate a consistent increase in portfolio returns—from 5.2% in 2000 to 11.8% in 2025—accompanied by a significant reduction in annualized volatility, declining from 8.1% to 3.0%. Concurrently, the portfolio’s sustainability score improved from 0.45 to a full alignment score of 1.00, reflecting a strategic shift towards high-impact green assets. Building on these observed trends, this study introduces the Eco-Financial Resonance Theory (EFRT), an original conceptual framework that interprets sustainable transitions as emergent phenomena arising from resonant interactions among four interdependent domains: financial flows, technological innovation, policy and regulation, and environmental outcomes. Scenario analyses highlight the pivotal roles of policy ambition and innovation pathways in shaping long-term risk-return profiles, with optimistic forecasts projecting returns exceeding 40% by 2050, alongside markedly reduced risks. Regional analysis reveals persistent disparities, underscoring the necessity for context-specific strategies to enhance systemic coherence. Beyond its theoretical contributions, EFRT offers actionable insights for investors and policymakers aiming to align profitability with ecological sustainability. Collectively, these findings position green finance not merely as a niche or ancillary activity but as a transformative mechanism for enabling scalable and resilient sustainability transitions amid accelerating global environmental challenges.